Cores Project - Conservation of endangered orchids: an action plan for conservation of Brazilian orchids - Nicoletti Fraga, Claudio (Universidad de Costa Rica, 2015)
The Cores Project, intent to collect biological and antropic informations on nine species of orchids that are included on the official list of threatened species of Brazil (Cattleya schilleriana, Laelia fidelensis, L. lobata, L. grandis, L. jongheana, L. virens, L. perrini, L. tenebrosa and L. xanthina) aiming to revaluate its conservation status and elaborate an action plan to each one in particular.